MALAY VOCABULARY LEARNING STRATEGIES PRACTICED BY FORM ONE NON-NATIVE STUDENTS - Gopinat A/L Muthy; Selvajothi A/L Ramalingam; Chew Fong Peng, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
Vocabulary plays an important role in language learning because it is the basis for mastering the language, especially for non-native speakers. Students face challenges in mastering vocabulary in Malay. This quantitative study aims to the vocabulary learning strategies among non-native speakers. This study involved a total of 254 students from 10 secondary schools in the Pudu and Bangsar areas of Kuala Lumpur through purposive sampling. Research findings were analysed using SPSS software version 27. The finding of the social strategy is the highest strategy cognitive strategy is the lowest. Overall, the Malay vocabulary mastery strategy is at a moderate level. This study suggests the aspect of vocabulary teaching should be given attention in Teaching and Learning activities starting from primary school.